2021
DOI: 10.1002/its2.62
|View full text |Cite
|
Sign up to set email alerts
|

Simulated traffic on turfgrasses during drought stress: II. Soil moisture, soil compaction, and rooting

Abstract: Turf is often subject to traffic stresses during drought. Our objectives were to evaluate the impacts of golf cart traffic applied during simulated drought on soil properties and turfgrass rooting. Soil and roots in the upper profile (0-30.5 cm) were evaluated in two cool-season (C 3 ) [Kentucky bluegrass (Poa pratensis L.) and perennial ryegrass (Lolium perenne L.)] and two warm-season (C 4 ) turfgrasses {buffalograss [Buchloë dactyloides (Nutt.) Engelm.] and zoysiagrass (Zoysia japonica Steud.)} maintained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Interestingly, trafficked perennial ryegrass had as high of GC as the two trafficked C 4 turfgrasses at the end of the drought in 2015, while trafficked Kentucky bluegrass had considerably lower GC (18–22%) than the other three trafficked turfgrasses. In a companion paper (Braun et al, 2021), we reported that golf cart traffic during drought had a minimal impact on soil and root characteristics as a result of decreasing soil moisture of this same experiment. It was also found that the C 4 turfgrasses and perennial ryegrass had larger root diameters, which may have led to greater capabilities of exploring large volumes of soil, thus better drought performance.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Interestingly, trafficked perennial ryegrass had as high of GC as the two trafficked C 4 turfgrasses at the end of the drought in 2015, while trafficked Kentucky bluegrass had considerably lower GC (18–22%) than the other three trafficked turfgrasses. In a companion paper (Braun et al, 2021), we reported that golf cart traffic during drought had a minimal impact on soil and root characteristics as a result of decreasing soil moisture of this same experiment. It was also found that the C 4 turfgrasses and perennial ryegrass had larger root diameters, which may have led to greater capabilities of exploring large volumes of soil, thus better drought performance.…”
Section: Resultssupporting
confidence: 51%
“…Data were collected from 26 June to 18 Sept. 2015 and 23 June to 15 Sept. 2016 from two 1.8‐ by 0.21‐m areas (tire width = 0.216 m) within each 1.8‐ by 1.4‐m plot including nontrafficked treatment plots. To evaluate the impacts on soil from and the responses of roots to traffic applied during a drought period, soil and root measurements conducted prior to and after termination of the drought and recovery periods are discussed in a companion paper (Braun et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…During a 41‐d dry down with no irrigation or precipitation in Manhattan, KS, green cover generally remained higher in ‘Paragon GLR’ perennial ryegrass than ‘America’ Kentucky bluegrass including when golf cart traffic was applied (Braun et al., 2021). Those authors reported that better performance in perennial ryegrass was strongly correlated to its larger root diameter compared with Kentucky bluegrass (Braun, Bremer, & Hoyle, 2022). Root parameters were not measured below 30 cm in that study, but in a drought study in Columbia, MO (silt loam soil; warm temperate, no dry season, hot summer [Cfa] climate [Kottek et al., 2006; Rubel et al., 2017]), root mass was greater in ‘Manhattan’ perennial ryegrass than in ‘Fykling’ Kentucky bluegrass below 36 cm (Sheffer et al., 1987).…”
Section: Interspecies Variationmentioning
confidence: 99%